2009
DOI: 10.1590/s1676-26492009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitudes on epilepsy among undergraduate health care students in Southern Brazil

Abstract: OBJECTIVE: To evaluate the awareness on epilepsy among undergraduate health care students in a private university. METHODS: A self-administered questionnaire about epilepsy was applied to 417 students at Universidade de Caxias do Sul. The answers were analyzed in two groups: group 1, medical and nursing students; group 2, psychology, physiotherapy and nutrition students. RESULTS: Most of the students were familiar with the disease. Although many of them recognize brain disease as a cause of seizure, it was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
3
12
1
Order By: Relevance
“…2.22% of medical students in this study consider it a self limiting disease in comparison to a study in Brazil where 1% of the students consider it as a self limiting disease [16].…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…2.22% of medical students in this study consider it a self limiting disease in comparison to a study in Brazil where 1% of the students consider it as a self limiting disease [16].…”
Section: Discussioncontrasting
confidence: 62%
“…Undergraduates being future medical practitioners must be evaluated at an early stage of their career regarding this aspect. When medical undergraduates were asked about the treatment of epilepsy, about 56.66% medical students responded that epilepsy is treated by medications, a similar study in Brazil shows that 93% of medical students are aware that epilepsy requires treatment by allopathic medications [16], this comparison shows that the medical undergraduates in this study group lack essential information concerning the drug treatment for epilepsy, and must be trained accordingly.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…13 The mistaken belief of putting shoe/onion on an epileptic person's face, placing bunch of keys in hands or other practices has been observed in more than 16% of students (Group A). In a study by Falavinga A et al, 14 these mistaken ideas were observed in 38.8% of the sample. Another Brazilian study 11 demonstrated that 71% of the first year students of health care related disciplines and 32% of the last year students follow these practices.…”
Section: Attitudementioning
confidence: 89%